Kolaborasi Konsultan Interior dan Tim Kontruksi Dalam Manajemen Proyek Desain (Jurnal iSpectrum, 2025)
Collaboration between interior consultants and construction teams plays an important role in the smooth and successful interior design project. In design project management, effective synergy between these two parties is a key factor to ensure that the planned design can be realized according to the client's expectations, both in terms of aesthetics and functionality, as well as within the constraints of the specified budget and time. Interior consultants are responsible for designing spaces that meet the client's functional and visual needs, while the construction team ensures that the design can be technically realized, paying attention to structural aspects, safety, as well as meeting applicable building standards. Therefore, intensive and coordinated communication between the two parties is essential to avoid miscommunication that can lead to design changes, delays, or cost overruns. Successful interior design project management requires the involvement of both parties in every stage of the project, ensuring that the final design not only reflects the creative vision, but can also be realized with high quality and in the right time. In this context, collaboration between an interior consultant and a construction team is not just about the division of tasks, but also about building a mutually supportive professional relationship for the success of a design project.